Impact of Work Life Balance and Work Culture on Employee Engagement - Salvi, Anil (Global journal of Business and Integral Security, 2025)
The thesis titled ‘Impact of Work-Life Balance and Work Culture on Employee Engagement’ investigates the intricate relationships among work-life balance (WLB), organizational work culture, and employee engagement. Understanding these dynamics is essential for enhancing employee engagement and driving organizational success, especially as modern competitive corporate environments increasingly prioritize productivity and employee well-being. Regression analysis is one of the quantitative research methods used in this study to examine the relationships and effects of various variables on employee engagement. The results show that work-life balance and work culture significantly and favorably affect employee engagement. Employee engagement is found to be significantly correlated with work-life balance, which explains a significant portion of the variation in employee engagement. Workload and organizational support are also found to be powerful indicators of employees’ emotional and psychological dedication to their employment. A healthy personal life and a positive workplace culture are also crucial, though their effects differ in strength. The study also demonstrates that work culture and work-life balance have a strong and statistically significant impact on employee engagement when combined. This suggests that organizational leaders should prioritize creating a positive work environment while also making sure that employees maintain a healthy work-life balance. According to the study, in order to increase employee engagement, organizations should place considerable emphasis on achievable workloads, supportive management techniques, and a healthy personal life. Workload management and organizational support have been found to be important indicators of employee engagement, but a balanced personal life is also significant. Employee engagement is also greatly impacted by organizational culture, which encompasses elements like creativity, openness, employee-driven culture, trust, and harmony. According to the study, an encouraging work environment is essential for developing an engaged workforce, and each element has a distinct impact on employee motivation and commitment. Furthermore, work culture and work-life balance have a strong combined impact on employee engagement, with both contributing significantly to the variance in employee engagement. The findings emphasize the significance of corporate policies that promote work-life balance and foster an innovative, cooperative, and honest environment. By adding elements like organizational support, work culture, and a healthy personal life to current employee engagement models, this study provides insightful theoretical implications. It also offers managers and HR specialists helpful advice on how to create and carry out policies that promote an environment that encourages high employee engagement. The study concludes by suggesting more research that might look at the impact of cultural variations on employee engagement across industries or the influence of other organizational characteristics. By offering an improved understanding of the primary factors influencing employee engagement, this study adds to the expanding body of knowledge in organizational behavior and builds the groundwork for future theoretical developments as well as practical management techniques represented to improve employee performance, engagement and satisfaction. Keywords: Work Life Balance, Work Culture, Employee Engagement, Exploratory Factor Analysis, Regression Analysis.